2017
DOI: 10.3844/ajavsp.2017.150.158
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease and Current Treatment Options in Dogs

Abstract: Inflammatory Bowel Disease (IBD) is an idiopathic and chronic gastrointestinal failure of cats, dogs and some farm animals such as horses. Since the long and difficult classical therapy of the disease has various side effects such as malignancy and lymphoma, new therapeutic methods are needed. However, a safe and standardized treatment protocol has not been developed, yet. Therefore, IBD treatment is still a big dilemma for both veterinary and human medicine. In this review, IBD and new possible therapeutic al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Gastrointestinal conditions characterized by abdominal pain, vomiting, and diarrhea are common signs in dogs. Chronic enteropathies (CE) in dogs are a heterogenous group of gastrointestinal (GI) disorders characterized by clinical signs that persist for at least 3 weeks or longer when other intestinal conditions such as parasitism or neoplasia have been ruled out 1,2 . CE in dogs is perceived to be a common presentation in all types of veterinary clinics with a prevalence reaching 18% based on databases obtained from general veterinary practices and insurance 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal conditions characterized by abdominal pain, vomiting, and diarrhea are common signs in dogs. Chronic enteropathies (CE) in dogs are a heterogenous group of gastrointestinal (GI) disorders characterized by clinical signs that persist for at least 3 weeks or longer when other intestinal conditions such as parasitism or neoplasia have been ruled out 1,2 . CE in dogs is perceived to be a common presentation in all types of veterinary clinics with a prevalence reaching 18% based on databases obtained from general veterinary practices and insurance 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of IBD in the present study was found to be 0.1 per cent (33 dogs) out of 30,535 diseased dogs presented to the Small Animal Medicine Unit with various ailments. However, Arslan (2017) stated that there is no information about incidence for IBD in dogs and cats. This is because, characterisation of many cases remains incomplete and detailed histopathological criteria for the medical diagnosis are needed.…”
Section: Resultsmentioning
confidence: 99%